Electroacupuncture combined with HDAC1 inhibitor suppress tumor growth via improving the recruitment of intratumor CD8+ T cells for triple-negative breast cancer in mice - Tian, Yehong; Ma, Yinjie; Li, Xue; Lu, Gang; Wang, Shixin; Qiu, Xiaowei; Du, Xu (Frontiers in Oncology, 2025)
Triple-negative breast cancer (TNBC) is known for its aggressive nature and poor prognosis, primarily due to limited treatment options stemming from immune evasion mechanisms. This study aimed to explore the therapeutic potential of peritumoral electroacupuncture (EA) in inhibiting tumor growth in TNBC, particularly focusing on the immune mechanisms related to CD8+ T cell recruitment and the involvement of histone deacetylase 1 (HDAC1) within the tumor microenvironment (TME). By constructing TNBC model in mice, we observed that EA not only inhibited tumor growth but also increased the presence of intratumoral CD8+ T cells and CCL5. Additionally, the expression of HDAC1 was found to down-regulate by EA. Remarkably, when EA was combined with the romidepsin (a class I HDAC inhibitor), a synergistic effect observed, leading to a greater increase in intratumoral CD8+ T cells compared to either treatment alone, resulting in a tumor inhibition rate of 60.03%. Importantly, EA did not worsen systemic inflammation, as serum levels of pro-inflammatory cytokines remained stable throughout the intervention. These findings indicate that peritumoral EA can effectively enhance anti-tumor immunity within the TME by down-regulating HDAC1. This research highlights the potential of combining non-invasive therapies like EA with pharmacological agent as a promising strategy for improving outcomes in the management of TNBC, warranting further exploration of its clinical applications.